1994
DOI: 10.1104/pp.104.3.857
|View full text |Cite
|
Sign up to set email alerts
|

Isocitrate Lyase and Malate Synthase Genes from Brassica napus L. Are Active in Pollen

Abstract: To investigate if pollen possesses glyoxysomal function, we analyzed the activities of isocitrate lyase and malate synthase genes. Because the activities of these enzymes were exceedingly low in pollen extracts, we constructed fusion genes encoding j3-glucuronidase (CUS) that are regulated by isocitrate lyase or malate synthase promoters from Brassica napus L. to increase the sensitivity of our assays. Expression of the fusion genes in transgenic tobacco was qualitatively similar to that of the endogenous gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
46
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 30 publications
5
46
0
Order By: Relevance
“…Details of identified enzymes of specific metabolic pathways, e.g. isocitrate lyase for the glyoxylate cycle (Zhang et al, 1994) or an alcohol dehydrogenase active in ethanolic fermentation (Mellema et al, 2002), are given in Supplemental Table S2, with the corresponding sequences accessible via the Sequence Read Archive of the European Nucleotide Archive (http://www.ebi.ac.uk/ena/data/view/ ERP002303; accession no. ERP002303).…”
Section: Identification Of Enzymes Of Metabolic Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of identified enzymes of specific metabolic pathways, e.g. isocitrate lyase for the glyoxylate cycle (Zhang et al, 1994) or an alcohol dehydrogenase active in ethanolic fermentation (Mellema et al, 2002), are given in Supplemental Table S2, with the corresponding sequences accessible via the Sequence Read Archive of the European Nucleotide Archive (http://www.ebi.ac.uk/ena/data/view/ ERP002303; accession no. ERP002303).…”
Section: Identification Of Enzymes Of Metabolic Pathwaysmentioning
confidence: 99%
“…So far, one may postulate that the metabolism of pollen is similar to that of sporophytic tissue if marker enzymes of specific metabolic pathways were identified, e.g. isocitrate lyase and malate synthetase for glyoxysomal function (Zhang et al, 1994). But detailed studies may reveal that at least parts of the pollen metabolism might be different due to its specific physiological role as suggested by Colaço et al (2012).…”
mentioning
confidence: 99%
“…There is some disagreement in the literature as to whether the glyoxylate cycle operates in growing pollen tubes, dependent on the species examined (Zhang et al, 1994;Mellema et al, 2002). However, examination of microarray data indicates that transcripts encoding the glyoxylate cycle enzymes isocitrate lyase and malate synthase are virtually absent from pollen and indeed also from other floral tissues in Arabidopsis (Zimmermann et al, 2004).…”
Section: Pollen Tube Germination and Growth Are Impaired In Cts Mutantsmentioning
confidence: 95%
“…Although there are several isocitrate lyase genes in Brassica napus L., we showed that at least one gene is active during seed development, postgerminative growth, and pollen maturation (Zhang et al, 1993(Zhang et al, , 1994. We also demonstrated that the 3.5 kb of DNA upstream of this gene contains sufficient information to specify its expression at each of these diverse developmental stages (Zhang et al, 1993(Zhang et al, , 1994. Thus, a single isocitrate lyase gene can be expressed at several stages of the life cycle.…”
mentioning
confidence: 99%
“…One hundred microliters of 0.5 mM luciferin (Sigma, diluted from a 10 mM stock in 1 mM Tricine, pH 7.8) was injected into the reaction mix, and the amount of light emitted within the first 10 s after luciferin injection was recorded using a Moonlight 2010 luminometer (Analytical Luminescence, San Diego, CA). GUS assays were performed as described by Zhang et al (1994). …”
mentioning
confidence: 99%